164 UK/ireland interim results from a DMF pregnancy registry. Issue 12 (14th November 2019) - Rog, David; Seferta, Nicola; McGuigan, Christopher; Everage, Nicholas; Jones, Cynthia
Abstract : Introduction: Data regarding delayed-release dimethyl fumarate (DMF) use, an approved MS treatment, in pregnant women is limited. United Kingdom (UK) and Ireland are enrolling DMF-exposed pregnant women into TecGistry, an ongoing prospective, observational registry to assess pregnancy outcomes. Methods: Pregnant women with MS exposed to DMF since the first day of their last menstrual period prior to conception or at any time during pregnancy were included. The UK and Ireland Coordinating Centres (Manchester Centre for Clinical Neurosciences and St. Vincent's University Hospital, Dublin) liaise directly with DMF-exposed patients and their HCPs. Results: As of 24 April 2018, 220 patients (11 patients from UK/Ireland) were enrolled; 161 pregnancy outcomes were reported: 147 (91.3%) live births, 14 (8.7%) spontaneous abortions (< 22 weeks). In UK/Ireland, 9 outcomes were reported: all live births, 8 full term, none premature (details pending on 1 case). Globally, 4 adjudicator-confirmed birth defects were reported: pyloric stenosis (1), transposition of the great vessels (1), ventricular septal defect (2; 1 in UK/Ireland). No maternal, neonatal, perinatal, or infant deaths were reported. Conclusions: Consistent with previous reports, there was no safety signal for DMF exposure on pregnancy outcomes based on ongoing registry results. Support: Biogen; disclosures to be included on poster.